Evaluation of leishmanin skin test reaction in different variants of cutaneous leishmaniasis - Giti Sadeghian; Hengameh Ziaei; Leila Shirani Bidabadi; Mohammad Ali Nilforoushzadeh (Wolters Kluwer Medknow Publications, 2013)
Introduction: Cutaneous leishmaniasis (CL) is a parasitic disease which has different clinical forms. The aim of this study is to compare the response to leishmanin skin test (LST) in three forms of CL including plaque type, lupoid type, and sporotrichoid type. Materials and Methods: This was a descriptive cross-sectional study. The patients enrolled in this study had three clinical forms of CL confirmed by positive smear of their lesions and then LST was performed for them. Results were categorized as negative (0-5 mm induration), positive (6-14 mm), and strongly positive (≥15 mm). The data were documented in the patients' files and analyzed with SPSS windows software version 16 (Inc.Chicago, USA). Results: 200 patients were enrolled in the study. In the group with plaque type, 86% had a positive LST, 13.3% were negative, and 0.7% were strongly positive. In the lupoid group, these figures were 45.8%, 8.4%, 45.8%, respectively. In the sporotrichoid group, LST was positive in 27.3%, negative in 72.7%, and none of the patients had a strongly positive reaction ( P < 0.05). Discussion: The most of the positive LST were belong to plaque and lupoid groups, the most of strongly positive were belong to lupoid, and the most of negative LST were related with sporotrichoid type. Conclusion: It can be suggested that lupoid and sporotrichoid types of CL are parts of a continuous spectrum of the disease with an enhanced cellular immunity in lupoid form and a decreased state in sporotrichoid type.